Role conflicts and coping strategies of academic entrepreneurs in an immature entrepreneurship environment - Zhaohui Yin; Xiaomeng Jiang; Peiru Tong (Humanities & Social Sciences Communications)
Abstract Academic entrepreneurs (AEs) often face role conflicts, particularly in immature entrepreneurial environments such as China, where competing role expectations create tensions. This study delves into the role conflicts and coping strategies of AEs at a Chinese university. Responding to the literature’s call for a symbolic-interactionist perspective on role theory, the study draws insights from interviews with both AEs and key university stakeholders, highlighting the importance of social interactions in shaping role expectations. The findings reveal that AEs experience both inter-role conflicts (tensions among their roles as researchers, educators, and entrepreneurs) and inter-sender conflicts (arising from disparate expectations of university stakeholders). While AEs employ diverse strategies to manage these conflicts, some approaches may inadvertently exacerbate tensions, fostering distrust within the university community. The study underscores the need for effective strategies to nurture a healthier academic entrepreneurship ecosystem. It makes theoretical contributions as one of the first to examine the interaction between inter-role and inter-sender conflicts in the context of academic entrepreneurship within an immature entrepreneurial environment. Practical suggestions are also provided at individual, institutional, and policy levels. These findings enhance understanding of the unique spatial context of academic entrepreneurship and inform better practices for managing the university faculty engaged in entrepreneurial activities.